Construção de um instrumento para determinação de viscosidade por meio da compressão de fluido entre placas planas - Silva, Diego Vieira da [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
The ascension of the electronic press, which uses processed materials in liquid form, brings the need of control of the viscosity of the materials to obtain films with such quality that is needed to produce devices with a rich performance. That being said, usual methods to determine of the viscosity, such as Stokes method, turn out to be expensive for demanding too much use of electrical material. Starting from this, this study focus on creating a viscometer that gives small parts of a certain quantity of material to determine its viscosity. With this instrument, a viscosity of the fluid it's determined through the measurements of the speed when compressed in two plates of glass. The resolution, the precision and the accuracy of the measurements performed with this instrument were evaluated from trying made, for the determination of the viscosity of honey. From these experiments, it was determined that the experimental material has a resolution of 23%, precision of 50% and 27% with capillary adjustment and accuracy of 47%. Besides the high uncertainty of the measurements, that limits the use of the instruments, it shows the possibility of create quantitative avaliations of viscosity by compressing the fluid of parallel plates of glass.

A ascensão da eletrônica impressa, que utiliza materiais processados na forma liquida, traz a necessidade do controle de viscosidade dos materiais para a obtenção de filmes com a qualidade necessária para a produção de dispositivos com elevado desempenho. Neste sentido, métodos convencionais para a determinação de viscosidade, como o método de Stokes, se tornam de alto custo por demandarem o uso de volumes elevados dos materiais eletrônicos. Partindo deste problema, este estudo tem como objetivo a construção de um viscosímetro que empregue pequenas quantidades de material para determinação de sua viscosidade. Com este instrumento, a viscosidade do fluido é determinada por meio de medições da velocidade de escoamento do material quando comprimido entre duas placas de vidro. A resolução, precisão e exatidão de medições realizadas com este instrumento foram avaliadas a partir de ensaios feitos para a determinação da viscosidade do mel. Destes experimentos, verificou-se que o aparato experimental possui resolução de 23%, exatidão de 47% e precisão de 50% e de 27% com ajuste de capilaridade. Apesar da elevada incerteza das medições, que limitam a utilização do instrumento, foi demonstrada a possibilidade de realizar avaliações quantitativas de viscosidade por meio da compreensão de um fluido entre placas paralelas.
Construction of an instrument for determining viscosity by compressing fluid between flat plates
Keywords: Viscometer; Measuring instruments; Fluid; Viscosímetro; Instrumento de medida; Fluido